Self-reflection in Games - The Representation of the Individuation Process in Celeste and Persona 2: Innocent Sin - Tavares, Amanda C. R.; Mota, Rosilane Ribeiro da; Melo, Walter (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2021: Anais Estendidos do XX Simpósio Brasileiro de Jogos e Entretenimento DigitalDO - 10.5753/sbgames_estendido.2021.19640, 2021)
Video games are popular nowadays, possessing the potential to positively impact people by alleviating unpleasant emotions, giving them leisure and empowerment. Understanding psychological factors can aid in building meaningful and engaging gameplay, resulting in more beneficial impacts on players and desirable video games. This work analyzes how the games Persona 2: Innocent Sin and Celeste use core concepts from Analytical Psychology mixed with the Hero’s Journey to build compelling narratives and gameplay. Game designers should not recognize these ideas as fixed rules but as an inspiration to create meaningful video game experiences and, consequently, aid the player’s transformation.